Evaluation of Hospital Management Information System (HMIS) Implementation in the Registration Unit from the Perspectives of Technology, Human, and Organization - Anggraeni, Riana Fitria; Prakoso, Bakhtiyar Hadi; Alfiansyah, Gamasiano; Mudiono, Demiawan Rachmatta Putro (International Journal of Healthcare and Information Technology, 2024)
Hospital X is currently undergoing a system transition from an old Hospital Management Information System (HMIS) to a new and more advanced version. This study aims to evaluate the implementation of HMIS in the registration section by examining three key aspects: technological, human, and organizational, using the HOT-Fit (Human, Organization, and Technology-Fit) framework. This research employs a qualitative analysis approach, with data collected through interviews, observations, and documentation. The findings from the technological aspect indicate that system development has been adapted to meet user needs; however, user manuals or clear operational guidelines are still lacking. HMIS is capable of providing information that aligns with both user and organizational requirements. From the human aspect, HMIS supports staff in completing tasks more efficiently, and users generally accept the transition to the new system, although training has not been distributed evenly among all personnel. The organizational aspect reveals that HMIS delivers relevant information to support both internal and external organizational functions. The use of HMIS in the registration unit contributes positively to the overall quality of hospital services, and optimal system performance benefits both users and the organization. Based on the results, it is recommended to schedule regular training sessions, increase staffing in the IT unit, establish specific policies governing HMIS usage, and conduct routine system maintenance to support sustainable implementation.